2021
DOI: 10.3390/transplantology2040044
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Hypothermic and Normothermic Perfusion in Kidney Transplantation

Abstract: Hypothermic and normothermic machine perfusion in kidney transplantation are purported to exert a beneficial effect on post-transplant outcomes compared to the traditionally used method of static cold storage. Kidney perfusion techniques provide a window for organ reconditioning and quality assessment. However, how best to deliver these preservation methods or improve organ quality has not yet been conclusively defined. This review summarises the promising advances in machine perfusion science in recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…This difference may indicate impaired cortical kidney perfusion, stemming from damaged capillaries and decreased renal filtration in damaged kidney allografts. A previous study ( 25 ) showed that cortical perfusion was lower in renal allograft recipients with low eGFR, while 2-4 weeks after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…This difference may indicate impaired cortical kidney perfusion, stemming from damaged capillaries and decreased renal filtration in damaged kidney allografts. A previous study ( 25 ) showed that cortical perfusion was lower in renal allograft recipients with low eGFR, while 2-4 weeks after transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to compare these machines and the published results because they differ in terms of the temperature used, oxygen and nutrient supply, duration of perfusion, and technical details such as pulsatile or non-pulsatile perfusion, automation and monitoring. No scientific trials have directly compared the use and efficacy of one apparatus to that of another [ 27 - 31 ].…”
Section: Kidney Preservationmentioning
confidence: 99%
“…That is why new perfusion technologies are being considered. Developments in hypothermic (HMP) and normothermic machine perfusion (NMP) technologies have shown potential in clinical kidney transplantation [18]. HMP involves the use of a mechanical pump to circulate cold preservation fluid in the graft, while during NMP, the graft is perfused at near-physiological temperatures and pressures, allowing cellular metabolism and function to be restored.…”
Section: Figurementioning
confidence: 99%